Online patient simulation training to improve clinical reasoning: a feasibility randomised controlled trial - Plackett, Ruth; Kassianos, Angelos P.; Kambouri, Maria; Kay, Natasha; Mylan, Sophie; Hopwood, Jenny; Schartau, Patricia; Gray, Shani; Timmis, Jessica; Bennett, Sarah; Valerio, Chris; Rodrigues, Veena; et al. (My University, 2020)
Online patient simulations (OPS) are a novel method for teaching clinical reasoning skills to students and could contribute to reducing diagnostic errors. However, little is known about how best to implement and evaluate OPS in medical curricula. The aim of this study was to assess the feasibility, acceptability and potential effects of eCREST - the electronic Clinical Reasoning Educational Simulation Tool.
Keywords: Clinical reasoning; Virtual patient; Simulation; Online learning; Medical students; Medical education; Feasibility study